Development of Crimean bakeries - Dunda, Svetlana (My University, 2013)
The analysis of development of Crimean bakeries is performed.
Keywords: development; enterprise; bakeries; розвиток; підприємство; хлібопекарні підприємства; развитие; предприятие; хлебопекарные предприятия; кафедра економіки праці та менеджменту